Upgrading The Early Childhood Education Teacher Capacity in Introducing English with A Simulation Strategy - Bambang Harmanto; Ida Yeni Rahmawati (ELLITE, 2022)
This study was conducted to explore the changes in Early childhood education teachers’ capacity when they were joining a special training with simulation strategy for introducing English at an early childhood education. Teacher’s capacity included two aspects in terms of English teaching strategies, developing material and media.  Developmental study was applied for implementing the strategy involving 10 early childhood education teachers. In the first meeting, they still felt difficult in implementing the model. In the second meeting finally they could practice it well. Quantitatively, 90% of respondents acknowledged and admitted that the simulation strategy  which they used have helped them to practice introducing English to young learners. Meanwhile, the 10% of respondents said that it was quite helpful for them. It can be concluded that training with simulation strategy was effective to improve early childhood education capacity in introducing English earlier. The successful model can be recommended for the other early childhood education teachers as a source of teaching for their students.